Modelling and Adaptive Control of a Yeast Fermentation Process inside a Fed-batch Bioreactor - Dan Selisteanu; Monica Roman; Emil Petre; Dorin Sendrescu (International Journal of Applied Methods in Electronics and Computers, 2015)
This work presents several issues concerning the modelling, kinetic estimation and nonlinear control of a baker’s yeast process that takes place inside a fed-batch bioreactor (FBB). First, a nonlinear model of the bioprocess is presented taking into consideration two approaches: the classical modelling scheme and the bond graph method. Second, to reconstruct the missing on-line kinetic information, estimation strategies are proposed. Finally, by using the process dynamical model and the on-line estimation strategies, an adaptive control scheme is designed in order to maintain a certain level of ethanol concentration, regardless of uncertainties and disturbances. This objective is attained by designing an adaptive controller as a combination between a linearizing control law and a high-gain observer. Numerical simulations are provided to illustrate the behaviour of the proposed estimation and control techniques.